Experience with dupilumab in patients with atopic dermatitis - E. A. Glukhova; E. D. Kuvshinova; V. A. Revyakina (Аллергология и Иммунология в Педиатрии)
According to recent data, the key molecules in the pathogenesis of atopic dermatitis are the cytokines IL-4 and IL-13, which initiate and maintain Th2 inflammation. Targeted therapy with dupilumab inhibits the signaling function of these cytokines by binding to the IL-4Rα subunit, which is part of the IL-4 and IL-13 receptor complexes. The drug is approved for the treatment of patients over 6 years of age with moderate to severe AD. The efficacy and safety of dupilumab have been confirmed by the results of clinical studies.   Materials and methods. 27 children with severe AD at the age of 8–18 years were under constant supervision. All patients received systemic treatment with dupilumab, topically used topical glucocorticosteroids (if necessary), emollients (twice a day). Dosing of dupilumab was carried out according to the instructions for the drug.   Results. After 26 weeks of complex therapy, 96,3 % of patients achieved an IGA index value of 0/1 and an improvement of 75 % according to the EASI-75 index. The SCORAD index dropped from an average of 78,8 points to 13,7. The average value of total IgE after 6 months decreased by 1518 kU/l. In 2 (7,4 %) patients, conjunctivitis was noted, which was not a reason to discontinue the drug.   Conclusion. During treatment with dupilumab, there is a significant decrease in the severity of the main symptoms of atopic dermatitis, including itching, exacerbations.